2004
DOI: 10.1128/jb.186.20.6938-6943.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Studies with Escherichia coli MelR Protein: Applications of Chromatin Immunoprecipitation and Microarrays

Abstract: Escherichia coli MelR protein is a transcription activator that is essential for melibiose-dependent expression of the melAB genes. We have used chromatin immunoprecipitation to study the binding of MelR and RNA polymerase to the melAB promoter in vivo. Our results show that MelR is associated with promoter DNA, both in the absence and presence of the inducer melibiose. In contrast, RNA polymerase is recruited to the melAB promoter only in the presence of inducer. The MelR DK261 positive control mutant binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 15 publications
(17 reference statements)
2
87
0
Order By: Relevance
“…Genome-wide identification of in vivo targets of bacterial DNA-binding transcriptional regulatory proteins have been limited to a handful of examples (Laub et al 2002;Molle et al 2003a,b;Eichenberger et al 2004;Grainger et al 2004). Moreover, these experiments typically involved microarrays containing PCR products representing only coding sequences, and hence do not represent an unbiased or comprehensive identification of in vivo targets of a DNA-binding protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide identification of in vivo targets of bacterial DNA-binding transcriptional regulatory proteins have been limited to a handful of examples (Laub et al 2002;Molle et al 2003a,b;Eichenberger et al 2004;Grainger et al 2004). Moreover, these experiments typically involved microarrays containing PCR products representing only coding sequences, and hence do not represent an unbiased or comprehensive identification of in vivo targets of a DNA-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide identification of in vivo targets of bacterial DNA-binding transcriptional regulatory proteins has been performed in a few cases (Laub et al 2002;Molle et al 2003a,b;Eichenberger et al 2004;Grainger et al 2004), but these experiments typically involved microarrays containing PCR products representing only coding sequences, and hence do not represent an unbiased or comprehensive identification of in vivo targets of a DNA-binding protein. In experiments designed to address the topological domain structure of the E. coli chromosome, it was shown that expression of the restriction enzyme EcoRI in E. coli cells results in at least partial cleavage of the majority of recognition sites (Postow et al 2004).…”
mentioning
confidence: 99%
“…This so-called ChIP-Chip technology was initially established in yeast (Ren et al, 2000), but has recently been applied to various bacterial systems (Grainger et al, 2004;Herring et al, 2005;Bruscella et al, 2008;Engels et al, 2008;Uyar et al, 2009). Considering the smaller size of bacterial genomes, the technology could be even more powerful in studying genome-wide binding and gene expression regulatory systems in bacteria.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…NimbleGen 60-mer arrays tiling over 36 Mb of the Drosophila genome at 100 bp resolution also have been used [39]. Binding by Escherichia coli TFs has been examined using off-the-shelf Affymetrix E. coli antisense arrays [40], while NimbleGen tiling arrays have been used to map E. coli RNA Pol binding sites [41].…”
Section: Chip-chipmentioning
confidence: 99%